PLACES OF USE AND CLASSIFICATION OF AGRICULTURAL TERMS IN ARTISTIC TEXT - Makhmudova Dilafruz Alijonovna (Bright Mind Publishing, 2025)
The article discusses the fact that the linguopoetic and linguocultural properties of agricultural terms in a literary text, in connection with the artistic thinking of the creator, act as metaphorical transfers or as a part of analogical devices and fulfill the linguopoetic purpose, therefore, it is appropriate to determine the semantic properties of agricultural terms, like words, in the context of the text.
Keywords: Terms, agricultural terms, literary text, linguopoetic, linguocultural, metaphor, artistic and aesthetic whole, poetic actualization.